Ethnochemistry Supports 21st Century Skills: Systematic Literature Review - Munawwarah; Ashari, Ayu (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This research aims to identify and analyze the contribution of ethnochemistry in supporting the development of 21st-century skills within the context of chemistry education. This study is important because many studies identify ethnochemistry as a highly potential field, but few have thoroughly examined how ethnochemistry can be applied to support the development of 21st-century skills. Using a Systematic Literature Review (SLR) approach, this research collects and evaluates relevant literature on the relationship between ethnochemistry and 21st-century skills. Thirteen articles were selected from a pool of 79 collected articles. Several 21st-century skills supported by the articles include scientific literacy, chemical literacy, critical thinking skills, and problem-solving abilities. The analysis shows that the dominant 21st-century skills supported are scientific literacy (46%) and chemical literacy (38%). These percentages are obtained by comparing the number of articles for each skill with the total number of articles analyzed. The conclusion of this study is that the 21st-century skills supported by ethnochemistry include scientific literacy, chemical literacy, critical thinking skills, and problem-solving abilities. However, there are still limitations: firstly, most studies are local and contextual; secondly, most studies use short-term designs, without long-term follow-up; thirdly, research instruments in several studies are limited to questionnaires and student perceptions, without data triangulation. This study recommends further research into the integration of ethnochemistry to support 21st-century skills such as critical thinking, problem-solving, creativity, collaboration, and others. Moreover, it is necessary to integrate ethnochemistry into the chemistry education curriculum, incorporating ethnochemistry as part of the teaching method that can enrich the teaching material with local cultural contexts.